Cycle helmets and the prevention of injuries. Recommendations for competitive sport - Thompson, D. C.; Patterson, M. Q. (Sports Medicine, 1998)
The scientific evidence that bicycle helmets protect against head, brain and facial injuries has been well established by 5 well designed case-control studies. Additional evidence of helmet effectiveness has been provided from time series studies in Australia and the US. Bicycle helmets of all types that meet various national and international standards provide substantial protection for cyclists of all ages who are involved in a bicycle crash. This protection extends to crashes from a variety of causes (such as falls and collisions with fixed and moving objects) and includes crashes involving motor vehicles. Helmet use reduces the risk of head injury by 85%, brain injury by 88% and severe brain injury by at least 75%. Helmets should be worn by all riders whether the cyclist is a recreational rider or a serious competitor engaged in training or race competition. The International Cycling Federation (ICF) should make the use of helmets compulsory in all sanctioned races.